2020
DOI: 10.3390/app10072374
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of a Supercritical Fluid Extract of the Halophyte Mesembryanthemum nodiflorum L. from Sicilian Coasts: Nutraceutical and Cosmeceutical Applications

Abstract: The aim of this paper was to obtain different extracts from the aerial parts of Mesembryanthemum nodiflorum, comparing traditional extraction (using solvents with increasing polarity such as hexane, ethanol 80%, acetone 70% and water) with an eco-friendly technique (supercritical fluid extraction (SFE)); to evaluate which extract showed a higher amount of antioxidants and then evaluate the bioactive properties in vitro, in human fibroblast (HS68). From the six extracts obtained it was observed that the solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Since it appears to be well documented the positive relationship between polyphenol content of plants extracts and their antioxidant activity in vitro [11,23,25,[61][62][63][64], the high content of total phenolic compounds found in Gd-E4 extract, may explain its activity against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Since it appears to be well documented the positive relationship between polyphenol content of plants extracts and their antioxidant activity in vitro [11,23,25,[61][62][63][64], the high content of total phenolic compounds found in Gd-E4 extract, may explain its activity against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Bueno-Silva et al [ 69 ] evaluated the effect of season on chemical composition and found lower formononetin contents (78.76 to 112.78 μg/g) than those found in this study for ethanolic extract of red propolis of the same origin. This may demonstrate that SFE (CO 2 as the solvent and ethanol as the cosolvent) may be an important and promising technology for obtaining red propolis extracts with potential for nutraceutical and cosmetic applications [ 70 ]. In the present study, it was possible to demonstrate that ethanol (as a cosolvent) played a role by causing an increase in the polarity and eluting power of supercritical CO 2 , maintaining the same process parameters without significantly changing selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The total antioxidant power of PH and Pep was measured using the DPPH assay [ 66 , 67 , 68 ]. A total of 0.4 mL of different Pep, at concentration of 1, 2, and 4 mg/mL, was prepared by diluting the stock solutions in absolute ethanol (30 mg/mL); they were then mixed with 1.6 mL of 100 μM DPPH in 96% ethanol to start the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Different concentrations of Pep (25, 50, and 75 µg/mL dissolved in sterile distilled water and filtered in 0.22 µm Millipore membrane) (Millex ® Merck Millipore, Darmstadt, Germany), were added to cells and incubated for 48 h. After 48 h, all samples except for the control were exposed to the chemical promoter of oxidative stress, hydrogen peroxide (50 µM) (Carlo Erba reagents, Milano, Italy), according to a previously standardized protocol [ 11 , 66 , 68 , 73 , 74 , 75 , 76 ]. The viability was measured using the 3-(4,5-dimethyl-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, according to Mossman’s method [ 77 ], as reported by Messina et al [ 11 ].…”
Section: Methodsmentioning
confidence: 99%